Pengaruh Machiavellian, Love of Money dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak - Moh. Rayudha Mahendra; Umaimah Umaimah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the influence of machiavellian, love of money, tax knowledge on taxpayer compliance. This type of research is quantitative research. The population of this research is individual taxpayers who do business in the Gresik area. The sampling method in this research is the purposive sampling method, namely the selection of samples based on predetermined criteria and obtained as many as 52 respondents. The data used in this research is primary data using a distributed questionnaire. The analytical method used is multiple linear regression analysis using the IMB SPSS Statistics 25 program. The results of this research indicate that the Machiavellian and love of money variables have no influence on taxpayer compliance and tax knowledge influences taxpayer compliance